1989
DOI: 10.3382/ps.0680510
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Concurrent Stressors in Chicks.

Abstract: Effects of multiple concurrent stressors on Hubbard x Hubbard chicks (Days 10 to 17 posthatch) were studied in a 2(6)-factorial experiment employing as treatments aerial ammonia (A, 0 or 125 ppm), beak trimming (B, sham handled or beak trimmed/cauterized), coccidiosis (X, gavage with 0 or 6 x 10(5) sporulated Eimeria acervulina oocysts), intermittent electric shock (E, 0 or between 2.9 and 8.7 mA), heat stress (H, 30.4 or 34.8 C), and continuous noise (N, 80 or 95 dB). Packed-cell volume (PCV) was decreased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…For instance, newts injected with hydrocortisone did not exhibit altered N:L ratios until 3 days post-injection, whereas some frogs responded within 12-144 h of injection (Bennett and Harbottle, 1968). In addition, a study in poultry demonstrated prolonged elevation of H:L ratios even after corticosterone concentrations had returned to baseline levels (McFarlane et al, 1989), similar to our observations in hellbenders. Although N:L ratios are often used as an indicator of acute stress in individuals when it is difficult to obtain enough blood to analyze for corticosterone (Davis et al, 2008), N:L ratios may not be a good surrogate for detecting stress responses in hellbenders over short time scales (i.e.…”
Section: Relationship Between N:l and Corticosterone Responsessupporting
confidence: 75%
“…For instance, newts injected with hydrocortisone did not exhibit altered N:L ratios until 3 days post-injection, whereas some frogs responded within 12-144 h of injection (Bennett and Harbottle, 1968). In addition, a study in poultry demonstrated prolonged elevation of H:L ratios even after corticosterone concentrations had returned to baseline levels (McFarlane et al, 1989), similar to our observations in hellbenders. Although N:L ratios are often used as an indicator of acute stress in individuals when it is difficult to obtain enough blood to analyze for corticosterone (Davis et al, 2008), N:L ratios may not be a good surrogate for detecting stress responses in hellbenders over short time scales (i.e.…”
Section: Relationship Between N:l and Corticosterone Responsessupporting
confidence: 75%
“…These were subjected to statistical analyses. Results for all leukocyte traits except H/L (reported here) are reported elsewhere (McFarlane et al, 1989b). Statistical Analysis.…”
Section: Introduction Materials and Methodsmentioning
confidence: 99%
“…Unlike the glucocorticoid response to stress, which starts within 2-5 min after a stress event (Romero and Reed 2005), changes in the leukocyte population in the peripheral blood are not evident until 1-2 h afterwards (e.g., Dhabhar et al 1995;Cirule et al 2012) and remain altered longer than plasma glucocorticoid levels (McFarlane et al 1989). However, the timing of these responses varies among taxa (Romero and Reed 2005;Davis et al 2008).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%